IMPLEMENTASI PERATURAN DAERAH NOMOR 6 TAHUN 2013 TENTANG LARANGAN, PENGAWASAN, PENERTIBAN DAN PENJUALAN MINUMAN BERALKOHOL DI SAMARINDA - Nur Mahyati Rahmini (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTOrdinary people also know that when we consume alcoholic beverages without limitation, the human becomes uncontrollable and always do as they wish it. Many cases - legal cases arising from the liquor. Problem drinking in New York City is not something new for the community. The habit of drinking has been popular in the community and is something that is difficult to overcome, until-until law enforcement officers become tired or bored seeing this situation. On the other side than the influence of liquor causing many problems in social life. Various examples of cases impact pretty much liquor, ie the occurrence of various types of crimes of violence, among others, for example, assault, theft, adultery / obscene / moral, destruction, rape, pembunuhaan, make noise at night, stopping the taxi asked for money to buy liquor, ask for money to passers-by in front of them, drinking in public places and so forthThe research method used in this research is normative juridical that legal research conducted by the norms and rules and regulations, especially with regard to Regional Regulation No. 6 Year 2013 On Prohibition, Monitoring, Control and Sale of Alcoholic beverage In SamarindaResults of research conducted in the field there are still places that do not have permission Sales of alcoholic beverages in the city of Samarinda, both overt and hidden -selling alcoholic beverages. This is a violation of Implementation of Regional Regulation No. 6 Year 2013 On Prohibition, Monitoring, Control and Sale of Alcoholic beverage In Samarinda.Based on the research results and the real conditions which exist, the authors conclude Implementation Regional Regulation No. 6 Year 2013 On Prohibition, Monitoring, Control and Sale of Alcoholic beverage In Samarinda has been implemented by the government of Samarinda Cq. Civil Service Police Unit of Samarinda but not as expected.Obstacles encountered in the implementation In the implementation of the Regional Regulation No. 6 Year 2013 On Prohibition, Monitoring, Control and Sale of Alcoholic beverage In Samarinda because certain elements that become Becking and low adherence to the law and legal compliance communityKey Word  : Regional Regulation No. 6 Year 2013 - Prohibition, Monitoring, Control and Sale of Alcoholic beverage In Samarinda